(3GdYed HGdCSWQdGH GdcQi hYLGFHgs - (3CMeO Hf YHO Gddg, MHT GdMGSH GdeQhRjs
(3ChdgG (B:s
(3jQjO Cf jHjf cja fSJYjf YjGfkG ai GdCSWQdGH GdcQi HYV eG GSJeO Ydjg ef GNJdGa Gddjd hGdfgGQ hGdeWGdY ai NW GdESJhGA s
(3BNQgG (B:s
(3hCeG GdCYeGd GdHGbjI ajg eKd EbGeI GdWGdY hGdeQGcR hGdOGFQ heG TGcd Pdc aEf GdCYeGd ajg cGdYed HPGJ GdUaGFM ShGA hHGddg GdYhf hGdJhajb s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfjs
(3HgG fXGe GdJYbjHIs
(3cJHJ Hbde eged GdfbW CMjGfkGs
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK (B(3475( 2(3C(B)) s
Keywords: (3Gdadcs